Oncological Outcomes of Adjuvant Radiotherapy for Partial Ureterectomy in Distal Ureteral Urothelial Carcinoma Patients - Li, Hong-zhen; Li, Xiaoying; Gao, Xian-shu; Qi, Xin; Ma, Ming-Wei; Qin, Shangbin (Frontiers in Oncology, 2021)
Purpose We retrospectively analyzed the oncological outcomes of T3 or G3 distal ureteral urothelial carcinoma (DUUC) underwent partial ureterectomy (PU) followed by adjuvant radiotherapy (ART). Methods From January 2008 to September 2019, clinical data from a total of 221 patients with pathologic T3 or G3 who underwent PU or RNU at our hospital were analyzed. 17 patients of them were treated with PU+ART, 72 with PU alone and 132 with radical nephroureterectomy (RNU). Clinicopathologic outcomes were evaluated. Survival was assessed using the Kaplan-Meier method. Cox regression addressed recurrence-free survival (RFS), metastasis-free survival (MFS), cancer specific survival (CSS) and overall survival (OS). Results Median age and follow-up time were 68 (IQR 62-76) years old and 43 (IQR 28-67) months, respectively. In univariate and multivariable analyses, no lymph node metastasis(LNM) and ART were independent prognostic factors of RFS (p=0.031 and 0.016, respectively). ART significantly improved 5-year RFS compared with the PU alone, (67.6% vs. 39.5%, HR: 2.431, 95%CI 1.210-4.883, p=0.039). There was no statistical difference in 5-year RFS between PU+ART and RNU groups (67.6% vs. 64.4%, HR=1.113, 95%CI 0.457-2.712, p=0.821). Compared with PU alone or RNU, PU+ART demonstrated no statistical difference in 5-year MFS (PU+ART 73.2%, PU 57.2%, RNU69.4%), CSS (70.7%, 55.1%, 76.6%, respectively), and OS (70.7%, 54.1%, 69.2%, respectively). Conclusions For distal ureteral urothelial carcinoma patients with T3 or G3, adjuvant radiotherapy could significantly improve recurrence-free survival compared with partial ureterectomy alone. There was no significant difference between survival outcomes of PU+ART and radical nephroureterectomy.